The Special Partnership: Considering U.S.- Saudi Relations Through the Alliance Politics Literature - Omar, Mohammed (Université d'Ottawa | University of Ottawa, 2017)
U.S.– Saudi Arabia relations are the longest running U.S. partnership in the Middle East. As a relationship between states with considerably different political systems, world views, and cultures, its viability has been the subject of reoccurring debate. More recently apparent fissures in the partnership over the Iran nuclear accord and counter-extremism in the Middle East, have led to louder questions about its future viability. Nonetheless, as the May 2017 visit by U.S. President Donald Trump to Riyadh shows, the relationship appears to be as strong as ever. This paper examines the unique parameters of the U.S.-Saudi relationship that have ensured its stability, in the face of clear divisions and disagreements. It does this through reviewing the alliance politics literature and using its framework to better understand U.S.-Saudi relations. Second, it establishes the key drivers of the U.S.-Saudi partnership in their economic, military, and security realms. Finally, the paper considers the impact of both the Iran nuclear accord and the election of President Donald Trump on the relationship. This comprehensive approach helps establish how a relationship between partners with opposing values, remains drawn closely together through shared interests.